How is Students’ Attitude Towards Learning English? : A Case Study at the Second Graders of SMP Islam Al-Falah Jambi - J, Syilvia Wenny (STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
This study investigates students’ attitudes and perceptions toward learning English at SMP Islam Al-Falah Kota Jambi. Attitude plays a crucial role in language acquisition, influencing students' engagement, motivation, and overall learning outcomes. The study examines three key aspects of students’ attitudes: behavioral, cognitive, and affective. Using a qualitative research approach with Yin’s case study method, data were collected through questionnaires and interviews with second-grade students. Findings reveal that students generally hold a positive cognitive attitude toward learning English, recognizing its importance for future careers and global communication. Behaviorally, students demonstrate responsibility in completing tasks but show varying levels of motivation for independent learning. The affective aspect highlights enthusiasm for English learning but also identifies challenges related to speaking confidence and anxiety. The study suggests that fostering a supportive learning environment, integrating interactive methods, and encouraging speaking practice can enhance students’ attitudes and learning outcomes. This study elucidates the subtle aspects related to students' attitudes, so enhancing English language education through the provision of contextually pertinent teaching methodologies and fostering the advancement of more effective learner-centered strategies. Future research should explore motivational factors, teaching strategies, and the impact of digital resources on language learning.